The Effect of Giving Chicken Liver Flour and Mung Bean Flour Pie on Hemoglobin Levels in Anemic Adolescent Girls - Gusti Cantika Amanda Putri; Ahmad Sadiq; Yunita Nazarena; Eliza; Yulianto; Sartono; Podojoyo (JURNAL RISET GIZI, 2026)
Background: Anemia remains a significant public health problem, particularly among adolescent girls in Indonesia. This condition is characterized by low hemoglobin levels in the blood, which can impair concentration, reduce productivity, and negatively affect reproductive health. One strategy to address this problem is through interventions using locally available food sources, such as pais formulated from chicken liver flour (a source of heme iron) and mung bean flour (a source of non-heme iron). To enhance iron absorption, the intervention was fortified with vitamin C derived from orange topping. Objective: This study aims to analyze the effect of Pikhaya consumption on improving hemoglobin levels among anemic female students at SMA Muhammadiyah 1 Palembang. Methods: A quasi-experimental design with a two-group pretest–posttest approach was employed. A total of 50 tenth-grade students were selected as participants and assigned into two groups: the intervention group (provided with an 80 g pai per day for 10 consecutive days, accompanied by nutrition education) and the comparison group (received nutrition education only). Results: The mean hemoglobin level in the intervention group increased from 9.57 g/dL (pre-intervention) to 10.76 g/dL (post-intervention), with a mean difference of 1.19 g/dL. Statistical analysis revealed a significant difference between the intervention and comparison groups (p-value = 0.000; α < 0.05). Conclusion: The administration of pikhaya has been proven effective in increasing hemoglobin levels among anemic adolescent girls at SMA Muhammadiyah 1 Palembang.